Prognosis of chronic kidney disease in patients with non-alcoholic fatty liver disease: a Northeastern Taiwan community medicine research cohort - Ting-Shuo Huang; I-Wen Wu; Chih-Lang Lin; Yu-Chiau Shyu; Yuen-Chan Chen; Rong-Nan Chien (Biomedical Journal, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with incident chronic kidney disease (CKD). We aimed to investigate outcomes and risk factors of CKD progression and regression. Methods: This is a longitudinal community-based cohort study of patients with NAFLD. Exclusion criteria included alcoholic liver diseases, sero-positive for hepatitis B surface antigen, sero-positive for hepatitis C virus antibodies, fatty liver index <60, individuals with only one year of data, missing data for fibrosis-4 score (FIB-4 score) and NAFLD fibrosis score (NFS), and advanced CKD at baseline. Main outcomes were stratified according to estimated glomerular filtration rate (eGFR) and albuminuria categories as state 1 (low risk), state 2 (moderately increased risk), and state 3 (high-risk/very-high risk of progression). The multi-state Markov model was used for outcome analysis. Results: This study included 1628 patients with NAFLD with a median follow-up of 3.4 years. State 2 CKD was found in 9.3% of patients at 5 years (95% CI, 8.1%–10.6%). Most patients with state 2 CKD recovered to state 1 (69%; 95% CI, 63.7%–74%), while 17.6% progressed to state 3 (95% CI, 13.4%–22.7%). Advanced liver fibrosis was found to be associated with the risk of transitioning from state 1 to state 2 ((FIB-4 score) ≥1.3; hazard ratio (HR), 1.42; 95% CI, 1.02–2.00), and reduced recovery from state 2 to state 1 (NFS≥−1.455; HR, 0.56; 95% CI, 0.34–0.91). Conclusion: NAFLD severity is associated with CKD, which may be reversible before becoming high-risk. Controlling metabolic risk factors and preventing advanced liver fibrosis are recommended.